IMPLEMENTASI METODE PROBABILITAS UNTUK ANALISIS PELUANG PENDAFTARAN MAHASISWA BARU BERDASARKAN POTONGAN DISKON DAFTAR ULANG - Fery Anugerah; Boy Rizki Akbar; Chelfina Utami; Muhammad Fahriza; Laila Maghfirah; Rian Farta Wijaya; Zulham Sitorus (CV. Hawari, 2026)
Competition among universities to attract new students has prompted educational institutions to implement effective promotional strategies, one of which is offering re-enrollment discounts to prospective students. This study aims to analyze the likelihood of new student enrollment based on the magnitude of re-enrollment discounts using a quantitative approach and historical data on new student admissions. The analysis employs a simple probability method to measure the likelihood of prospective students re-enrolling based on the discount category offered. The results show that an increase in the discount rate leads to an increase in the likelihood of new student re-enrollment, with the highest probability—0.79, or 79%—observed in the 30% discount category. The application of this probability method has proven to assist universities in formulating promotional strategies and supporting more effective decision-making in the new student admission process.